Knowledge and Calcium Intake to the Risk of Scoliosis at Boarding School Students (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2023)
Teenagers in the modern era often have improper sitting positions, which will affect posture abnormalities, namely scoliosis. Scoliosis occurs due to many factors, such as information obtained from knowledge. In addition, there are nutritional factors obtained from calcium intake because a deficiency will affect bone density. This study aims to understand the relationship between knowledge and calcium intake with the risk of scoliosis in adolescents. The method used was an analytic observational study and a cross-sectional study design. Thirty-five students were chosen by purposive sampling. The respondent checked using Adam Forward Bending Test Checklist and the Food Frequency Questionnaire (FFQ). All data were processed using SPSS. The results of the correlation test from the Spearman-rho test on the knowledge variable with a significance value of 0.309 (p0.05) and the calcium intake variable of 0.624 (p0.05) concluded that H1 was rejected and H0 was accepted, which means there is no relationship between knowledge and calcium intake on the risk of scoliosis in adolescents. This study concluded that there is no relationship between knowledge and calcium intake on the risk of scoliosis in adolescents. But the long-term effects of insufficient calcium intake need further investigation.